A guide on FIB preparation of samples containing stress corrosion crack tips for TEM and atom-probe analysis - Lozano-Perez, S (2008)
The preparation of samples containing stress corrosion crack tips for 3D atom-probe tomography and transmission electron microscopy is of ultimate importance for understanding the mechanisms controlling crack propagation. In this paper, it will be shown that a focused ion beam machine equipped with an in situ micromanipulator is an ideal tool to systematically prepare such demanding samples. The methodology is described and discussed in detail, and several results are presented to demonstrate the potential of the technique. © 2007 Elsevier Ltd. All rights reserved.